the high king - Alexander, Lloyo; Lloyd Alexander
The sword of Drynwyn, the most powerful weapon in the kingdom of prydain, has fallen into the hands of Arawn-Death-Lord. Now Taran, Assistant Pig-keeper, and prince Gwydion lead an army against the powerful lord. After a winter expedition filled with danger, Taran's forces arrive at Mount Dragon, evil's stronghold. There taran is forced to make the most crucial decision of his life as he confronts the evil enchantress Achren and the diabolical Arawn.